2020
DOI: 10.1039/d0dt00843e
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated charge transfer of Cd0.5Zn0.5S@ZnS core–shell nano-spheres via decoration of Ni2P and g-C3N4 toward efficient visible-light-driven H2 production

Abstract: Unique Cd0.5Zn0.5S@ZnS-Ni2P/g-C3N4 hybrid nano-spheres demonstrate enhanced photostability, improved light-harvesting and facilitated charge separation toward efficient H2 evolution from visible-light-driven water-splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…[4][5][6] PHE systems based on various kinds of semiconductors have been extensively investigated so far, [7,8] among which Pt/TiO 2 has been regarded as one of the most major photocatalysts. [9][10][11][12][13] To overcome the inherent defects of TiO 2 such as large band gap which leads to low photocatalytic efficiency, some research groups reported the development of dye-sensitized Pt/TiO 2 photocatalysts for hydrogen evolution. [14][15][16][17] A recent trend for sensitizing Pt/TiO 2 is the use of metal-free organic dyes with strong absorptivity and panchromatic sensitization properties.…”
mentioning
confidence: 99%
“…[4][5][6] PHE systems based on various kinds of semiconductors have been extensively investigated so far, [7,8] among which Pt/TiO 2 has been regarded as one of the most major photocatalysts. [9][10][11][12][13] To overcome the inherent defects of TiO 2 such as large band gap which leads to low photocatalytic efficiency, some research groups reported the development of dye-sensitized Pt/TiO 2 photocatalysts for hydrogen evolution. [14][15][16][17] A recent trend for sensitizing Pt/TiO 2 is the use of metal-free organic dyes with strong absorptivity and panchromatic sensitization properties.…”
mentioning
confidence: 99%
“…Notably, the Cd 0.5 Zn 0.5 S photocatalyst displays the lowest PL peaks which indicate that photon-generated carrier recombination of Cd 0.5 Zn 0.5 S can be more effectively inhibited, suggesting that porous Cd 0.5 Zn 0.5 S twinned phase junction nanosheets have superior hydrogen evolution activity. 44,45 Figure 7b exhibits the surface photovoltage (SPV) signal of Cd 1-x Zn x S (x = 0, 0.25, 0.5, and 0.75) photocatalysts. For semiconductors with similar components, the photovoltage intensity is positively correlated with the separation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Cd 1-x Zn x S solid solution exhibits much lower PL intensity, implying that the recombination of photo-induced e − /h + pairs is significantly inhibited. Notably, the Cd 0.5 Zn 0.5 S photocatalyst displays the lowest PL peaks which indicate that photon-generated carrier recombination of Cd 0.5 Zn 0.5 S can be more effectively inhibited, suggesting that porous Cd 0.5 Zn 0.5 S twinned phase junction nanosheets have superior hydrogen evolution activity 44,45. Figure7bexhibits the surface photovoltage (SPV) signal of Cd 1-x Zn x S (x = 0, 0.25, 0.5, and 0.75) photocatalysts.…”
mentioning
confidence: 99%
“…And photoexcited e − in the CB of g‐C 3 N 4 also got together on NiP for hydrogen production (Figure 13). [84] …”
Section: Application Of Tmps In Photocatalytic H2 Evolutionmentioning
confidence: 99%
“…And photoexcited e À in the CB of g-C 3 N 4 also got together on NiP for hydrogen production (Figure 13). [84] The absorption of visible light, which accounts for about 42 % of the total energy of sunlight, is also one of the key factors affecting photocatalytic activity. Therefore, the WPdecorated Zn x Cd 1-x S composite was prepared by Yan et al [83] to achieve strong visible light absorption.…”
Section: Tmp/zn X Cd 1-x Smentioning
confidence: 99%